A Review of Pediculosis Studies in Iran During Three Decades (1990-2020) - Mousa Khosravani; Shokat Ali Amiri; Azam Rafatpanah; Cobra Bandak; Roya Latifi; Mohammad Moradi; Nashmin Mohemmi; Fariba Abdollahi Harat; Seyed Mohsen Mohebbi Nodez; Zohreh Hatami (Shiraz University of Medical Sciences, 2021)
Abstract Background: Lice are obligate parasites that bring about some mild infestation or severe diseases on different parts of the human body. Head lice can easily spread in an overcrowded community with inadequate hygienic conditions. Also, it affects children's well-being and education programs. Methods: This study is a narrative review.  To carry out this comprehensive research about pediculosis in Iran, all published data on scientific research resources were included i.e.  Google scholar, Springer, ProQuest, JSTOR, Scopus, Web of Science, EBSCO, Bioline, BioOne, ScienceDirect, ResearchGate, PubMed, Sage, Wiley Online Library, World Scientific, and SID.   Results: Overall, 52,342 students (from primary and secondary schools) and around 20,000 adult persons were infested with P. capitis in Iran during 3 decades (1990-2020) as reported by published documents but the actual number may statistically be higher. The variation of results implies that risk factors are linked with numerous cultural, geographical, economic, and personal habits.  In general, the infestation rate of Pediculosis capitis in the south and southeast was higher than in other parts of Iran. Conclusion: Family members shouldavoid sharing hair tools particularly hairbrushes. Authors believe that not only economic situations but also some behaviors originating from personality traits influenced children's health. In this regard, children in higher grades might tend to conceal